Factors associated with age-related changes in oral diadochokinesis and masticatory function in healthy old adults - Se-Yeon Min; Nan-Sim Pang; Yu-Ri Kim; Sol-Ah Jeong; Bock-Young Jung (BMC Oral Health, 2024)
Abstract Background This cross–sectional study aimed to identify factors associated with age-related changes in masticatory performance (MP) and oral diadochokinesis (ODK) and to provide normal values in healthy old adults for the diagnosis of oral frailty. Methods A total of 385 participants were divided into three age groups (Gr1-3): 20–64 years, 65–74 years, and ≥ 75 years. To investigate tongue-lip motor function, ODK was assessed as the number of repetitions of the monosyllables /pa/ta/ka/. Four questionnaires were used to assess subjective masticatory ability, cognitive ability, and psychological status. MP, bite force, and occlusal area were tested to assess dynamic objective masticatory function, and the number of remaining teeth and functional tooth pairs were determined to assess static objective masticatory function. Handgrip strength (HG), oral dryness, and tongue pressure (TP) were assessed to identify influencing factors. Intergroup differences were evaluated by ANOVA and the Kruskal‒Wallis test, and correlations between ODK and orofacial factors were evaluated. Results This study revealed significant age-related declines in TP, HG, and ODK, especially after 65 years of age. Factors affecting MP were posterior teeth, the Eichner index, bite force, occluding area, the Korean Mini-Mental State Examination (KMMSE) score, and ODK. Each ODK syllable was associated with different factors, but common factors associated with ODK were MP, HG, and PHQ-9 score. For the syllables /pa/ta/, the Eichner Index, TP, and oral dryness were also associated. For the syllable /ka/ in Gr3, MP, TP, HG, oral dryness, and the KMMSE score were associated. Conclusions These results could provide practical guidelines for oral rehabilitation in old adults and contribute to improving the understanding of age-related changes in oral function and the multidimensional nature of masticatory dynamics.